HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN RAWAT JALAN DI PUSKESMAS BELAWAN - Yulina Yulina; Rapael Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2019)
Quality of service can be interpreted as conformity of professional standards with the utilization of resources effectively and efficiently, so that the needs of patients can be achieved optimal degree. Based on the Legatum Prosperity Index (2017) data which states Indonesia's global Health Index is ranked at 101 from 149 countries, this is because there are still many remote areas that are still difficult to access health care. Satisfaction to the quality of service as much as 51.0% of respondents who rate dissatisfied, such as the process of receiving the patient is served slowly, health officers do not timely come, and lack of hospitality of health officers in response to complaints Patients. The design of this research is an analytical survey with the Cross Sectional approach. The number of research populations is 98 outpatients. The sampling technique used is Purposive Sampling. Data retrieval using questionnaire measuring instrument. Analysis of data conducted in the analysis of Univariate and bivariate (test Chi-Square). The results of this study showed that the reliability with the P value is 0.042 < 0.05, the responsiveness with a value of P is 0.041 < 0.05, empathy with the value P is 0.015 < 0.05, and the guarantee with the value P is 0.042 < 0.05. Conclusions are reliability, responsiveness, empathy and assurance of having a relationship with patient satisfaction. It is hoped that Belawan health center to improve the service of reliability, responsiveness, assurance and empathy in Belawan Puskesmas.